Dr. Catalona's collection - Fisher, James (Ph.D); Guithues-Amrhein, Denise; Pieroni, Heidi (London : SAGE Publications: SAGE Business Cases Originals, 2018)
This case focuses on a dispute between Dr. William J. Catalona, a renowned prostate cancer researcher and surgeon, and his former employer, Washington University, over the ownership and control of an important collection of human tissue and blood. The case is further complicated by the fact that many of the individual donors--a significant portion of them former or current patients of Dr. Catalona--have been asked to take a position with respect to the disposition of the repository. The case raises important issues of informed consent in human medical research and explores the complicated relationships that exist among various stakeholders in such research. The case also presents insight into conflicts that develop with the commercialization of life science research. The conflicts introduce financial and administrative challenges that test the capacity of policies to anticipate and resolve among research institutions, their employees, and patients.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Catalona, William J; Conflict management; Business ethics; Research -- Moral and ethical aspects